Validity of the Reaction Time Concealed Information Test in a Prison Sample - Suchotzki, Kristina; Kakavand, Aileen; Gamer, Matthias (Frontiers in Psychiatry, 2019)
Detecting whether a suspect possesses incriminating (e.g., crime-related) information can provide valuable decision aids in court. To this means, the Concealed Information Test (CIT) has been developed and is currently applied on a regular basis in Japan. But whereas research has revealed a high validity of the CIT in student and normal populations, research investigating its validity in forensic samples in scarce. This applies even more to the reaction time-based CIT (RT-CIT), where no such research is available so far. The current study tested the application of the RT-CIT for an imaginary mock crime scenario both in a sample of adolescent prisoners (n = 27) and a matched control group (n = 25). Results revealed a high validity of the RT-CIT for discriminating between crime-related and crime-unrelated information, visible in medium to very high effect sizes for error rates and reaction times. Interestingly, in accordance with theories that criminal offenders may have worse response inhibition capacities and that response inhibition plays a crucial role in the RT-CIT, CIT-effects in the error rates were even elevated in the prisoners compared to the control group. No support for this hypothesis could, however, be found in reaction time CIT-effects. Also, performance in a standard Stroop task, that was conducted to measure executive functioning, did not differ between both groups and no correlation was found between Stroop task performance and performance in the RT-CIT. Despite frequently raised concerns that the RT-CIT may not be applicable in non-student and forensic populations, our results thereby do suggest that such a use may be possible and that effects seem to be quite large. Future research should build up on these findings one the one hand by increasing the realism of the crime and interrogation situation and by further investigating the replicability and the theoretical substantiation of increased effects in non-student and forensic samples.